Comparison of the results of the assessment of physical development with the data of the bioimpedance study of the body composition of secondary school students - I. E. Shtina; S. L. Valina; O. Yu. Ustinova (Сибирский научный медицинский журнал, 2025)
The assessment of a child’s physical development, including nutritional status, by the value of the body mass index is not always objective, since it does not take into account the component composition of the body.   The aim of the study is to compare the results of the assessment of physical development with the data of the bioimpedance study of the body composition of secondary school students.   Material and methods. Study groups included 165 girls and 170 boys aged 12 [10; 15] years (median [lower quartile; upper quartile]). All children were assessed for physical development in accordance with height SDS (standard deviation score), body mass index (BMI) SDS and bioimpedance analysis of body component composition. A comparative analysis of growth, BMI, body fat (BF %) and skeletal muscle mass percentage (SMM %) was carried out, taking into account gender and age.   Results. A comparison of growth SDS and BMI SDS, the structure of results of bioimpedance analysis deviations did not reveal statistically significant intergroup differences (p = 0.057–0.979). At the same time, it was found that in girls, compared to boys, the BF% is statistically significantly higher (by 1.3 times, p < 0.001), whereas the SMM % is less (1.2 times, p < 0.001). Girls were 1.5 times less likely to have low LM values (p = 0.024) and 1.4 times less likely to have high SMM values. A direct correlation was established between BMI SDS and the BF% in both sexes (r = 0.71–0.80; p < 0.001).   Conclusions. The assessment of physical development by the value of BMI SDS correlates with data on the body component composition. Bioimpedance analysis of body composition can be recommended as an additional method for assessing the nutritional status of children and adolescents.